Impact of COVID-19 on Medical Laboratory Workers in Libya: A Cross-Sectional Study - Eman Abdulwahed; Eida Elmansorry (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objectives. Healthcare workers are more vulnerable to COVID-19 infection than the general population due to frequent contact with infected individuals. However, Medical Lab workers at a higher risk of this contagious disease than those who work in other departments. This study aimed to analyze the perspectives of medical lab workers, in terms of the challenges, financial implications, fears, motivation, and satisfaction from organizational processes and policies adopted, amid the COVID-19 crisis. Methods. A cross-sectional study was conducted from March 25 to April 9, among Libyan Medical Lab workers in three public hospital laboratories. Data on participant characteristics were collected with a specifically designed questionnaire. The responses were recorded on a five-point Likert Scale (1 = strongly disagree, 2 = disagree, 3 = neutral, 4 = agree and 5 = strongly agree). The statistical analysis was performed using the Microsoft Excel 2019. Frequency and percentages were calculated for gender, experience, and designation while descriptive results based on the responses were also recorded. Results. The study yielded a sample size of 90 participants. Of these 66 (73%) reported that the current lifestyle adopted during the pandemic was not better than the traditional one. Around 72 (80%) of the responses were not fear of employment termination amid the COVID-19 crisis. However, financial challenges were being faced by 63 (70%) respondents. The quality of family life was improved in 48 (53%) cases while 54 (60%) were of the view that their social activities at work have suffered. Furthermore, 60 (67%) did not feel the same level of motivation to come to work every morning during the outbreak, as before. Similarly, 60 (67%) were not satisfied with the measures taking by the management during the outbreak. Conclusion. The results of this survey provide a laboratorians perspective during times of crisis and provide us certain lessons to plan for such unexpected circumstances in the future.